Endothelial-T cell crosstalk contributes to vascular injury in fatty liver disease. (14th October 2021) - Cheung, C; Ng, C Y; Lee, K L; Wu, K X; Chioh, F W J; Tan, K; Siau, A; Muthiah, M D; Chen, Q F; Tan, N S; Ng, H H; Dan, Y Y
Abstract: : Cardiovascular complications are often the fundamental causes of death in non-alcoholic fatty liver disease (NAFLD) patients. While there are known systemic mediators in NAFLD that may induce vascular inflammation, the mechanism of endothelial dysfunction remain understudied. In this work, we harnessed the replicative potential of blood outgrowth endothelial cells (BOECs) to develop personalized cell lines from NAFLD patients and healthy controls. Our transcriptomic analysis showed that the top interactome network enriched in NAFLD BOECs comprised of several C-C and C-X-C chemokine ligands involved in immune cell chemotaxis. We previously reported T cell infiltration in mouse model of non-alcoholic steatohepatitis, and here, we confirmed enhanced endothelial chemokine signatures in arterial histological sections. To elucidate endothelial-immune crosstalk, we performed single-cell analysis on human peripheral blood mononuclear cells and found T cell intensification in NAFLD patients compared to healthy controls. Our immunoprofiling by flow cytometry further revealed that NAFLD patients possessed higher levels CD8+ memory cells. Functionally, T cells, instead of monocytes, adhered more pronouncedly to NAFLD BOECs. In evaluating the CXCL12-CXCR4 axis in chemotaxis, CXCR4 antagonist (AMD3100) substantially modulated the migration of patient-derived CD8+ T cells towards NAFLD BOECs, which was not observed in healthy endothelial-T cell chemotaxis coculture. Finally, we validated NAFLD-associated endothelial dysfunction by enumerating two folds more circulating endothelial cells, a biomarker of vascular injury, in the blood samples of NAFLD patients than healthy controls. Our work provides insights for translation to restore blood vessel health and potentially mitigate adverse vascular events in NAFLD. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Industrial Alignment Fund Pre-Positioning grant from the Agency for Science, Technology and Research, Singapore